Prevalence and Determinants of Job Stress among Handloom Weavers in Rural Tamil Nadu: A Community-Based Cross-Sectional Study - Vijayakarthikeyan M; Kannan S, Raju; Kannan S, Thamarai; Sangeetha S; Grace, Angeline; Ritikaa S; Priya NK, Shakthe (National Journal of Community Medicine, 2026)
Background: Occupational stress is one of the key psychosocial risk factors impacting health, productivity and safety of workers in the informal handloom weaving sector mainly in rural India. The objectives of the study were to estimate the prevalence of job stress among weavers and to determine the sociodemographic and work-related factors associated with job stress. Materials and Methods: 530 weavers were enrolled using simple random sampling method. Validated New Job Stress Scale was used to assess job stress and based on the scores participants were classified into: low, moderate and high job stress. Data were analyzed by SPSS software (version 22) and prior ethical clearance was obtained. Results: Nearly 20.8% had poor work-life balance, 44.2% reported lack of coworker support, 13.4% participants had high job stress and 33.3% had moderate job stress. Male gender (AOR = 2.28, 95% CI: 1.08-5.01), work hours (AOR = 1.46, 95% CI: 1.01-2.23) and poor work-life balance (AOR = 9.98, 95% CI: 4.90-20.32) were the independent predictors of high job stress on multivariable analysis. Conclusion: Work place interventions that address regulated hours of work, supportive work environments and better balance between work life are necessary to protect mental health and ensure sustainable production in the informal textile sector.